(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The sensory innervation of the clavicle is complex, and the best regional block technology for clavicular surgery has yet to be determined. Compared with ultrasound-guided the superficial cervical plexus block and interscalene brachial plexus block, clavipectoral fascial plane block combined with superficial cervical plexus block for clavicular operation has longer postoperative analgesia, better preserves the motor function of the upper limbs and avoids the incidence of diaphragmatic paralysis. Purpose: Evaluation of anesthesia efficacy for surgery, motor blockade by MBS scale and postoperative pain by VAS scale. Methods: Prospective intervention case series. In June 2024, at Saigon ITO Phu Nhuan Hospital fascial plane block was performed at the medial third and lateral third of the clavicle, each side with 10 ml of Ropivacaine 0.375% and superficial cervical plexus anesthesia with 5 ml of Ropivacaine 0.375% under ultrasound guidance for 18 patients from 18 to 66 years old in surgery for fractures of the middle third of the clavicle. Results: The average time of sensory blockade was 2.23 minutes, the duration of pain relief was 410 minutes. All 18 patients were completely blocked for surgery with a VAS score of 0, reaching 100%. Motor unblocked in upper extremity (rate 100%), postoperative pain relief within 24-48 hours reached 100% without morphine with VAS < 4 points, patient satisfaction rate was 100%. Conclusion: Ultrasound-guided fascial plane block with ropivacaine is a new technique, easy to perform, safe, ensuring good anesthesia for surgery and pain relief after clavicle surgery without any side effects, patients are very satisfied.